Importancia y comentario a la carta de la Iglesia de Tiatira (Ap 2,18). Segunda parte - Caballero LC, José Antonio (Alpha Omega, 2010)
The current article continues a previous one (Alpha Omega 12 [2009], 221-236) on the importance and commentary on the letter to the Church of Thyatira. It focuses on the exegesis of Rev 2:18 and is divided into two parts. Part One examines the possibility of an episcopal interpretation of “Angel of the Church” and analyzes terms such as Thyatira and the command to write. Part Two studies the expression “Son of God” from an exegetical perspective along with other anthropological terms and references to parts of the human body—eyes and feet—in light of their Scriptural context and meaning.